先天性黑色素细胞痣的激光疗法:系统性评述. (14th February 2018) - Eggen, C.A.M.; Lommerts, J.E.; van Zuuren, E.J.; Limpens, J.; Pasmans, S.G.M.A.; Wolkerstorfer, A.
Abstract : Linked Article: Eggen et al. Br J Dermatol 2018; 178 :369–383